Characterization of a Capsule-Deficient Pasteurella multocida Isolated from Cygnus melancoryphus: Genomic, Phenotypic, and Virulence Insights - Nansong Jiang; Hongmei Chen; Weiwei Wang; Qizhang Liang; Qiuling Fu; Rongchang Liu; Guanghua Fu; Chunhe Wan; Yu Huang; Longfei Cheng (Microorganisms)
Pasteurella multocida is a zoonotic pathogen responsible for severe diseases in domestic and wild animals, posing threats to public health and causing substantial economic losses. Here, we describe a naturally attenuated P. multocida strain, FCF147, isolated from a mortality event involving black-necked swans (Cygnus melancoryphus) in a wildlife habitat in Fujian, China. Genomic and phylogenetic analyses revealed that FCF147 is evolutionarily distant from other P. multocida lineages and lacks the entire capsule gene cluster. Morphological observations revealed that the loss of the capsule exposed proteins on the bacterial surface. Phenotypic characterization demonstrated reduced capsule production, enhanced biofilm formation, and increased tolerance to heat stress. In vivo infection models confirmed that FCF147 exhibits markedly attenuated virulence in both mice and poultry. However, immunization with FCF147 did not provide effective protection against the challenge of a virulent capsular type A strain. These findings suggest that while FCF147 is poorly virulent, its ability to form robust biofilms and survive thermal stress may facilitate persistence in wild bird reservoirs and potential transmission routes. These findings offer novel insights into the ecological adaptation and pathogenic potential of naturally capsule-deficient P. multocida in wildlife, highlighting their relevance to wildlife surveillance and disease ecology.